IDENTIFICATION AND CLASSIFICATION EXAMINATION OF SUGAR FOR CUSTOMS DECLARATION USING ARTIFICIAL INTELLIGENCE TOOLS - TKACHENKO, Alina (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article analyzes the issue of identification and classification examination of sugar for the purpose of customs declaration using artificial intelligence tools. According to the results of the study, identification features of sugar were established by the raw materials used, depending on the manufacturing method and crystal size. The sample under study is white crystalline sugar made from sugar beet. Identification data were used to conduct a classification examination in order to determine the code according to the Ukrainian Classifier of Foreign Economic Activity Codes. It was established that the sample belongs to section IV “Ready-made food products; alcoholic and non-alcoholic beverages and vinegar; tobacco and its substitutes”. It was found that white crystalline sugar is classified in group 17 “Sugar and sugar confectionery”. It was established that crystalline sugar has the product code 1701991000. A classification examination of the identified product was carried out using artificial intelligence ChatGPT, Gemini, Claude (Anthropic). It has been proven that only ChatGPT artificial intelligence can be fully used to determine the product code (all others determined the code incorrectly), but even its capabilities are not enough in matters of identification. As a result of the study, a classification solution was formed, which is the basis for filling in columns 31 and 33 of the customs declaration. Based on the results of determining the product code, a certificate for the product was formed in the MDOffice program and tariff and non-tariff customs regulation measures were established. The import duty rate is 50%, but in accordance with interstate agreements it is zero for the import of sugar from the United Kingdom; EU countries (subject to quotas); for the purposes of the Armed Forces of Ukraine and other military formations for the period of martial law in the event of the import of goods by non-profit organizations. Non-tariff regulation includes the control of food products.
Keywords: identification; declaration of goods; classification examination; customs clearance; Ukrainian classifier of goods of foreign economic activity; food products; granulated sugar; artificial intelligence